Composição e estrutura da comunidade fitoplanctônica em lagoas de estabilização da Estação de Tratamento de Esgoto (ETE), Cascavel, Paraná, Brasil - Riediger, Wiviany (2013)
This work aimed to analyze the composition variation seasonal and structure of phytoplankton community in stabilization ponds in Sewage Treatment Station Rio das Antas in the city of Cascavel, noting the influence of environmental variables on this community. The collections of phytoplankton were carried in two points collection between March 2011 and February 2012. A total of 39 taxa were identified, being the most representative class Cyanobacteria both in richness and density. There was a low spatial and temporal variability in phytoplankton composition during the study period. The phytoplankton community showed up with low wealth but high density of species and was represented mainly by classes Cyanobacteria, Chlorophyceae. The Shannon diversity was classified as very low to low, and the equitability, in general, was high. The analysis of permutation of multivariate data showed that statistically the data density of affluence and phytoplankton between periods and sampling sites, to behave similarly. The variation distribution observed throughout the period of study, characterized by replacing, in proportions of Cyanobacteria by Chlorophyceae. The homogeneity of the distribution this species throughout the period of study between sampling sites, probably due to the similar characteristics of sites, comprising high concentration of organic matter, low energy hydrodynamic shallow and restricted circulation of water.